2014
DOI: 10.1177/039463201402700114
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with a Combination of Omalizumab and Specific Immunotherapy for Severe Anaphylaxis after a Wasp Sting

Abstract: Hymenoptera venom anaphylaxis after bee or wasp sting is a common problem that affects about 1.2 percent to 3.5 percent of the general population. Venom-specific immunotherapy (VIT) is an established mode of treatment for immunoglobulin (Ig) E-mediated Hymenoptera venom allergy. However, VIT may often be associated with immediate anaphylaxis which can lead to treatment withdrawal. Several cases published in recent years suggest that omalizumab, used as add-on therapy may be able to prevent anaphylaxis during V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 9 publications
(7 reference statements)
0
27
0
Order By: Relevance
“…Meanwhile, a number case reports have been published that report the use of omalizumab in Hymenoptera venom allergic patients on VIT . Treatment protocols using omalizumab in patients not tolerating VIT vary widely, and a standard regimen is not yet available; corresponding outcomes are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, a number case reports have been published that report the use of omalizumab in Hymenoptera venom allergic patients on VIT . Treatment protocols using omalizumab in patients not tolerating VIT vary widely, and a standard regimen is not yet available; corresponding outcomes are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…In some patients, omalizumab was found to prevent side‐effects of VIT. This prevention, however, required an ongoing omalizumab therapy . If the omalizumab dose was reduced, systemic reactions promptly recurred …”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, the minimal effective dose of omalizumab to protect from systemic reactions to VIT was 150 mg [10], thus the search of the protective dose should start from 150 mg, with increase to 300 mg and, possibly, to 450 mg in case of incomplete protection. The most appropriate combination therapy including also corticosteroids and antihistamines is not yet established and needs be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…While there have been no randomized controlled trials evaluating the addition of omalizumab to venom IT, several case reports and small patient series have been published on the use of omalizumab with venom IT, using a variety of treatment protocols with regard to both venom IT and omalizumab dosing . While some case reports have not shown benefit, most have suggested that the addition of pre‐treatment and/or maintenance omalizumab decreased the risk of systemic reactions during venom IT in high‐risk patients, including some individuals with mastocytosis …”
Section: Venom Immunotherapy + Omalizumabmentioning
confidence: 99%